The Utilization of Google Workspace to Improve the Poetry Analysis Skills of Tenth Grade Students at State Senior High School 2 Malang - Rahutami, Rahutami; Mathelda, Fince; Pudjastawa, Astrid Wangsagirindra (Paidea : Jurnal Pendidikan dan Pembelajaran Indonesia, 2025)
This research utilizes Google Workspace, especially Google Docs which is integrated with mobile phones, in learning poetry analysis in class X E State Senior High School 2 Malang. The goal is to increase students' active participation and understanding of the intrinsic elements of poetry, including themes, majas, and rhyme. This study uses the Kemmis and McTaggart model Classroom Action Research (PTK) approach which was carried out in two cycles with 36 students. Data was collected through classroom observations, teacher diaries, and online worksheet documents, then analyzed by data reduction techniques, data presentation, and conclusion drawn. The results showed an increase in student learning completeness from 22% in the pre-cycle to 61% in the first cycle and reached 86% in the second cycle. Real-time collaboration in Google Docs has proven effective in deepening understanding of the intrinsic elements of poetry and encouraging students' critical engagement. The novelty of this research lies in the application of Google Docs in the context of poetry analysis at the high school level, which has been more widely applied in writing or prose learning, so as to theoretically expand the use of digital platforms to strengthen the ability of online collaborative-based literary analysis, and practically provide an alternative technology-based literary learning strategy that is participatory, collaborative, reflective, and relevant to the learning needs of the century 21st.